Task and Relationship Orientation of Professionals in Afghanistan and Thailand - Bahaudin G. Mujtaba; Tipakorn Senathip; Jatuporn Sungkhawan (Business Ethics and Leadership)
The purpose of this paper is to analyze the leadership styles and approaches that are linked to Afghan and Thai respondents by exploring their task and relationship orientations to glean best practices for application in the war-torn nation of Afghanistan. To continue gathering more data, we have consistently been using Northouse’s Style Questionnaire to collect responses from different cultures over the past two decades. More specifically, for this latest study, we compared the leadership orientations of working adult respondents from Thailand and Afghanistan based on their nationality and socialization in each culture on the task and relationship-orientation continuum of leadership. To gain practical insights across these two Asian cultures, we reflect and explore the Afghan orientation and compare it with the cultural practices of people in Thailand, where politicians have managed their political affairs more peacefully with their neighbors. Both Afghanistan and Thailand’s cultures are rooted in thousands of years of Asian philosophies, and both are high-context and collective; therefore, people are presumed to be more relationship-oriented, and this study found statistically significant support for this presumption. While respondents from both countries do have a stronger focus on their relationships, data shows that their task orientation is significantly lower. Analysis, recommendations for inclusion training, dealing with societal / workplace mobbing, and the study’s limitations are presented toward the end of the paper. The findings are useful for training purposes with managers, political leaders, and expatriates working in these two South and East Asian countries. For example, currently the political leaders in Afghanistan are working with the international community to unite all Afghans so they can become less dependent on foreign forces to keep the country peaceful. As such, they can capitalize on their task and relationship orientation skills to work on this gigantic task. Similarly, as of May 2021, Thailand has been experiencing another wave of the Covid-19 coronavirus, with about 10,000 infection cases on some days; as such, Thai leaders have to build strong relationships with everyone in the country to effectively manage this task of limiting the spread of this deadly infection through strict quarantine rules and quick vaccination of their large population.